Competence-one term, various definitions: a scoping review for sports coach education and research - Möhrle, A. (International Sport Coaching Journal, 2025)
The competence of sports coaches is a key factor in athletes` sporting success. Mindful of this, sports coach education and research have placed considerable emphasis on competence in recent years. A lack of shared understanding around the concept complicates the endeavour, raising the following question: How is the term "competence" in relation to coaches defined in coach education and research? I sought to answer this research question via a scoping review. In database and internet searches, I obtained n = 1,912 hits and identified n = 14 sports coaching frameworks. Following title and abstract screening and full-text assessment, I conducted content analysis on n = 47 publications. The results indicate frequent use of the term, with few attempts to define it. Where definitions occur, they usually fall into one of two types: Type A, found in empirical studies written in English, describes the term in relation to their athletes` sporting success. Type B, found in all types of publications (theoretical, empirical and practical), defines it in terms of the knowledge and skills a coach requires in order to succeed in coaching situations. This paper concludes with a recommendation for a shared multi-faceted definition of "competence" in relation to coaches.